Sterile Gelatin Film Reduces Cortical Injury Associated With Brain Tumor Re-Resection. Issue 4 (29th December 2020) - Przybylowski, Colin J; So, Veronica; DeTranaltes, Kaylee; Walker, Corey; Baranoski, Jacob F; Chapple, Kristina; Sanai, Nader
Abstract: BACKGROUND: Recurrent intracranial tumors frequently require re-resection. Dural adhesions to the cortex increase the morbidity and duration of these revision craniotomies. OBJECTIVE: To describe the use of commercially available sterile gelatin film to prevent meningocerebral adhesions and decrease the rate of surgically induced ischemia from revision craniotomy. METHODS: This retrospective cohort study examined patients with recurrent glioma, meningioma, and metastasis who underwent re-resection at least 30 d following their initial tumor resection. Cortical surface tissue ischemia after re-resection on diffusion-weighted magnetic resonance imaging was compared for patients with (gelatin film group) and without (nongelatin film group) a history of gelatin film placement at the conclusion of their initial tumor resection. RESULTS: A total of 84 patients in the gelatin film group were compared to 86 patients in the nongelatin film group. Patient age, sex, tumor pathology, tumor volume, tumor eloquence, laterality of surgical approach, history of radiotherapy, and time interval between resections did not differ between groups. Radiographic evidence of cortical ischemia following reoperation was less prevalent in the gelatin film group (13.1% vs 32.6%; P < .01). In multivariate logistic regression analysis, no gelatin film ( P < .01) and larger tumor size ( P = .02) predicted cortical surface ischemia following revision craniotomy. Postoperative complications in the gelatin film and nongelatin film group otherwise did not differ. CONCLUSION: Routine placement of commercially available sterile gelatin film on the cortex prior to dural closure is associated with decreased surgically induced tissue ischemia at the time of revision tumor craniotomy.